Optimization Of Digital Library Services Using Artificial Intelligence (Ai): Approach To Green Library - Iqbal, Rahmat; Kesuma, Aghesna Rahmatika; Saputra, Julian Hadi; Amaliah, Eni (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Applying artificial intelligence (AI) in digital libraries can enhance operational efficiency and facilitate the implementation of green library concepts. This study aims to explore the potential of AI technology to optimize digital library services and support environmentally friendly principles. The data were gathered through a literature review and an observational study of the implementation of AI in various libraries. The qualitative descriptive approach was used to investigate how AI affects the automation of processes like cataloging and information retrieval and implementing chatbots for user interaction. The study's findings demonstrate that AI, encompassing natural language processing (NLP) search systems and chatbots, enhances the speed and accuracy of services while reducing reliance on printed materials and energy consumption. Furthermore, AI reduces carbon footprints by minimizing the physical storage space and energy consumption required for operations. The findings of this study indicate that the integration of AI in digital libraries not only enhances the efficiency of services but also supports environmental sustainability, making them more environmentally friendly and effective.